A evolução histórica do federalismo brasileiro e a centralização na figura da União pós-1988 - Costa, Fabio Alexandre (2015)
This dissertation presents tendencies of the Brazilian federalism after the promulgation of the 1988 Constitution.In order to achieve such objective, it is divided in three stages. Firstly, through a bibliographic review, it refers to the origins of federalism and the main schools which debate the theme. Many divergences between the schools are observed, but it emphasizes the consensus about there mark able characteristic of the federations: the decentralization which bestows autonomy on the federative entities. The focus of the second stage is the decentralization in the history of the Brazilian federalism. Regarding the passage from the unitary Empire to the federalist Republic, the dissertation draws mainly on accounts of important political men, contemporary with the transition process. Regarding the republican Brazil, it analyses the federal constitutions and other legal and extra legal instruments which gave form and materialized the federation. In addition to this analysis, the support of historians and political scientists contributes to develop an overview of the diverse phases of the Brazilian federalism. It is verified that there are conflicting opinions on the de facto autonomy of the federal entities, particularly during periods of dictatorships. In the third stage, the first step is an examination of the transition from military dictatorship to democratic rule and the work of the National Constituent Assembly, specially the debates concerning decentralization. The following investigation of the 1988 constitutional text reveals a federal arrangement that established the autonomy of four federal entities (federal, states, federal district and municipalities), cooperative, which decentralized revenue, but centralized powers. Then, the dissertation studies the dispersion of power between different levels of government regarding public finances, social policy, public security and self organization. It concludes that this arrangement, which was raised in an atmosphere conducive to decentralization, is marked by the coexistence with politically centralizing tendencies motivaded.